Steel fibers in the resistance to compression of the concrete (Gaceta Técnica, 2019)
This research aims at to evaluate the effect of steel fiber on concrete specimens under compressive strength. The compression strength test was determined in three groups with three specimens each, a control group and two experiments with proportions of 25 and 30 kg/m3 of steel fiber a compression test was made on the specimens at the age of 14 days. The results of the group with the highest resistance is that with a proportion of 25 kg/m3 of steel fiber with resistance 212,39 kg/m2, exceeding the control group by 1,1%
Keywords: concrete specimens; resistance to compression; fracture of specimens